Retail Investors Preferences in the Millennial Generation in Choosing the Index to Invest in the Indonesian Stock Market Approach to the Study of Phenomenology - Wisnu Mawardi; Muhammad Aziz Cahyana; Sasya Rahmitha (Budapest International Research and Critics University, 2021)
Investment is an activity that it must do as early as possible to fulfill its financial future. The purpose of this study is to find out the reasons why millennial retail investors decide to invest in the Indonesian stock market, find out the index preferences that millennial investors are interested in, find out the behavior of millennial retail investors who are successful and fail in making investment decisions and can be used as recommendations for a securities company if you want to make a stock mutual fund product for the millennial generation. The research method is carried out qualitatively with a phenomenological approach through semi-structured interview instruments with a millennial generation population and a sample of 10 retail investors. The study results show that millennial retail investors are interested in investing in the Indonesian stock market due to profit in the future. The index preference for millennial retail investors is the sector financial in the majority. Retail investors' are millennial generation success tends to multiply the workings of the stock market itself. In contrast, retail investors millennial generation, who fail, tends to follow the call of others without understanding the workings of the stock market itself. Suppose a securities company wants to make a stock mutual fund product among the millennial generation. In that case, the index recommendation is IDX-IC in the financials, consumer non-cyclical, properties, real estate, energy, and infrastructure sectors.